Recurrent Breast Sparganosis: Clinical and Radiological Findings - Park, Jiyoon; Woo, Ok Hee; Cho, Kyu Ran; Seo, Bo Kyoung (Journal of the Korean Society of Radiology, 2015)
We report a case of recurrent sparganosis of the breast within 6 months following surgical removal of worms from the breast. The patient was referred to our hospital with a palpable mass in the right breast. On admission, breast ultrasonography revealed a tortuous tubular hypoechoic lesion with indistinct margins within a surrounding hyperechoic area, which strongly suggested sparganosis. We performed surgical excision and confirmed sparganosis. After 6 months, the patient detected a new mass in her right breast and visited our hospital. Breast ultrasonography revealed similar features in a different area of the same breast. We confirmed recurrent sparganosis surgically. KCI Citation Count: 1